Morphological and phylogenetic analyses reveal two new species of the Fusarium fujikuroi (Hypocreales, Nectriaceae) species complex in China - Mingwei Zhang; Cheng Peng; Shuji Li; Chengming Tian (MycoKeys)
The Fusarium fujikuroi species complex (FFSC) encompasses a diverse array of more than 80 phylogenetic species with both phytopathological and clinical importance. A stable taxonomy is crucial for species in the FFSC due to their economical relevance. Fungal strains used in this study were obtained from Castanea mollissima and Rubus lambertianus, collected from Beijing and Shaanxi Province. We employ morphological and phylogenetic analyses based on partial gene fragments of the translation elongation factor 1-alpha (tef1), beta-tubulin (tub2), calmodulin (CaM), RNA polymerase largest subunit (rpb1), and RNA polymerase II second largest subunit (rpb2), as well as the pairwise homoplasy index tests. Studies have shown that these phylospecies are clustered in the Asian clade of the FFSC. The present study delineates two novel Fusarium species within the FFSC, named F. castaneophilum and F. rubicola, complemented by illustrations and descriptions.